The Impact of Urbanization and Natural Calamity to the Demise of Malay Settlement Along the River Fringe: Case Study of Malay Settlement Near Budor River in Kelantan - Azli, Abdullah (Universiti Malaysia Sarawak, 2024)
Human settlement issues are among the never-ending topics being debated. The studies on human settlements include multidisciplinary scopes including geography, sociocultural, economy, politics, and technology, making this field even wider in its study scope. Although various studies have been conducted on the issues of human settlements, the studies on Malay settlements are quite neglected. Initially, the Malay settlements existed within the vicinity of rivers as these were the main sources of living among Malay communities, including their transportation system. When Malaya achieved its independence, the development processes took place even more rapidly. The development at that time was more emerging and focused more on the urban areas. Owing to the infrastructure and facilities left by the British colonials, the urban population started to increase and thus escalated the demand for more urban settlements. Consequently, there was urban sprawl that targeted the Malay settlements at the river fringe. The situation was a threat to the settlements and the Malay communities due to the urbanisation processes, physically and mentally. From another perspective, natural calamity such as floods frequently happened and threatened the Malay communities. Without proper infrastructure, they were continuously hit with challenges in their lives and at their place of living. This study focused on the Malay settlements in Kota Bharu, Kelantan. This study aimed (i) to explore the impacts of the Malay settlements along the river fringe, (ii) to examine the pressures of urbanization and natural calamity on Malay settlements destruction, and (iii) to analyse the impacts of settlement destruction on architectural values and the future Malay settlements in the area. Eight Malay settlements in Kelantan River and Budor River were specifically selected as the case studies using a mixed method. Besides, a modern anthropology approach such as participant observation technique was combined with the observation techniques, visual analyses,mapping, photo tracking, land survey, journal and historical documents, and random interviews with 35 respondents who had been living for almost three generations at the study areas. Other than that, a total of 350 respondents who were also the locals were randomly selected to answer a questionnaire. All data were analysed using SPSS V21 software and cross-examnine with AutoCad 2020, Google Earth, Google Maps, Doxiadis’ Theory of Five Principle in Human Settlements, and literature review. The study found that the Malay settlements that based their living on the river-based activities had totally been destructed. Rivers were not the pride of the Malay communities anymore in developing themselves and their family economy. Moreover, the factors including natural calamity and urbanisation, plus the absence of the efforts from the government to preserve the Malay communities and their settlements in Kota Bharu, contributed to the destruction of Malay settlements that at the same time retarded the culture and identity of the Malays from enjoying the urban experiences. As a consequence, they were continuously living in challenges and found it difficult to compete with other races especially in terms of urban economies. Finally, they had to choose to either adapt with the urban development or move to other places. Although the approach of preservation of Malay communities has never been considered in Malaysia, this method is seen as an approach that could preserve the Malay settlements and communities to improve their neighbourhood quality and modern living, especially those living in the urban areas located in a rapidly developing country like Malaysia.